DATOS BIOLÓGICOS Y D ESCRIPCIÓ N DE ESTADOS INMADUROS DE EXOCHONOTUS EUGENIAE (C O LEO PTERA : CLERID A E: EN O PLIIN A E) (Acta Entomológica Chilena, 2022)
The association of Exochonotus eugeniae to plants of Euphorbia lactiflua affected by xylophagousinsects and their restricted geographic distribution in the Pan de Azúcar National Park (26°08’S), III Región,Chile, are recognized. A probable competitive displacement is suggested between Exochonotus eugeniaeand Inhumeroclerus thomsoni in the Coastal zone of the desert inhabiled by Euphorbia lactiflua. Themature larvae and the pupa of the species are described.
Keywords: Exochonotus eugeniae, Euphorbia lactiflua, geographical distribution, immalure stages, Cleridae, Chile